Spatio‐temporal transcriptome profiling and subgenome analysis in Brassica napus. (19th July 2022) - Wei, Lijuan; Du, Hai; Li, Xiaodong; Fan, Yonghai; Qian, Mingchao; Li, Yali; Wang, Huiyi; Qu, Cunmin; Qian, Wei; Xu, Xinfu; Tang, Zhanglin; Zhang, Kai; et al.
SUMMARY: Brassica napus is an important oil crop and an allotetraploid species. However, the detailed analysis of gene function and homoeologous gene expression in all tissues at different developmental stages was not explored. In this study, we performed a global transcriptome analysis of 24 vegetative and reproductive tissues at six developmental stages (totally 111 tissues). These samples were clustered into eight groups. The gene functions of silique pericarp were similar to roots, stems and leaves. In particular, glucosinolate metabolic process was associated with root and silique pericarp. Genes involved in protein phosphorylation were often associated with stamen, anther and the early developmental stage of seeds. Transcription factor (TF) genes were more specific than structural genes. A total of 17 100 genes that were preferentially expressed in one tissue (tissue‐preferred genes, TPGs), including 889 TFs (5.2%), were identified in the 24 tissues. Some TPGs were identified as hub genes in the co‐expression network analysis, and some TPGs in different tissues were involved in different hormone pathways. About 67.0% of the homoeologs showed balanced expression, whereas biased expression of homoeologs was associated with structural divergence. In addition, the spatiotemporal expression of homoeologs was related to the presence of transposable elements (TEs) and regulatory elements (REs); more TEs and fewer REs in the promoters resulted in divergent expression in different tissues. This study provides a valuable transcriptional map for understanding the growth and development of B. napus, for identifying important genes for future crop improvement, and for exploring gene expression patterns in the B. napus . Significance Statement: The study drew the global transcriptome map of 24 vegetative and reproductive tissues at six developmental stages in Brassica napus . And preferential expression analysis and subgenome dominance in relation to transposable and regulatory element content were performed.